2009
DOI: 10.1158/1078-0432.ccr-08-1067
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Classification and Prognostication of Adrenocortical Tumors by Transcriptome Profiling

Abstract: Purpose: Our understanding of adrenocortical carcinoma (ACC) has improved considerably, yet many unanswered questions remain. For instance, can molecular subtypes of ACC be identified?If so, what is their underlying pathogenetic basis and do they possess clinical significance? Experimental Design: We did a whole genome gene expression study of a large cohort of adrenocortical tissues annotated with clinicopathologic data. Using Affymetrix Human Genome U133 Plus 2.0 oligonucleotide arrays, transcriptional profi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
340
0
16

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 345 publications
(381 citation statements)
references
References 50 publications
25
340
0
16
Order By: Relevance
“…Giordano et al (2009) Whereas several findings support the relevance of cell cycle damage in adrenocortical tumorigenesis, no data have been published on the involvement of retinoic acid signalling to date. Here, we discuss the findings established by our meta-analysis and experimental CGH-transcriptomics study and present a review of these and previous observations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Giordano et al (2009) Whereas several findings support the relevance of cell cycle damage in adrenocortical tumorigenesis, no data have been published on the involvement of retinoic acid signalling to date. Here, we discuss the findings established by our meta-analysis and experimental CGH-transcriptomics study and present a review of these and previous observations.…”
Section: Discussionmentioning
confidence: 99%
“…By statistical analysis of microarray studies performed by Giordano et al (2009) and To¨mbo¨l et al (2009), we have identified 554 and 450 significant gene expression changes between NAs and ACAs, respectively: 46 of these were common. In the same studies, 2509 and 2564 significant gene expression changes between NAs and ACCs were found and 1017 of these were common.…”
Section: Meta-analysis Of Gene Expression Datamentioning
confidence: 92%
See 3 more Smart Citations